Delegation of Authority for Improving Organizational Performance in Indonesian Mining Sector - Suharyani, Yenny Dwi; Riyanto, Setyo; Nusranigrum, Dewi; Elmi, Farida (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study explores the role of delegation of authority in improving organizational performance within Indonesia’s mining inspection sector, emphasizing its alignment with Sustainable Development Goals (SDGs) 8, 9, and 16. Using a qualitative approach, data were collected from 20 key informants through semi-structured interviews, direct observations, and document analysis. Thematic analysis and triangulation ensured the reliability and validity of findings. The results, based on thematic analysis and triangulation, show that structured delegation leads to a 30% increase in decision-making efficiency and a 25% improvement in accountability, measured by response times, compliance rates, and inspector collaboration. Specifically, mining inspectors reported faster response times, higher compliance rates, and stronger collaboration across administrative levels. The study addresses a critical research gap by linking delegation practices with sustainable governance outcomes in a sector vital to Indonesia’s economy. While the research is context-specific, the findings provide operational insights into how delegation mechanisms contribute to both organizational effectiveness and national development priorities. The paper highlights practical implications for policymakers and organizational leaders, suggesting that delegation should be institutionalized as part of regulatory frameworks to achieve sustainable governance. Limitations include the qualitative scope and restricted sample, but the study offers a robust foundation for future mixed-methods research. By situating delegation of authority within the SDG framework, this study strengthens the relevance of organizational behavior research to global development discourse.